Automatic adapter cut off / Shahrul Naim Roslan, Ubaidullah Masnoor and Muhammad Afiq Naufal Mohd Nor - Roslan, Shahrul Naim; Masnoor, Ubaidullah; Mohd Nor, Muhammad Afiq Naufal (2013)
Due to the overdue charge of battery, they tend to swell and may explode if it is critically over the battery power storage limit. Typical charger did not have a current limitation supply and therefore the battery continue to charge as long as it is connected to the power supply. This will cause the battery to damage and broken. Hence, techniques to cut off the current supply to the battery were applied when it is full in order to save power consumption and battery lifespan.The usage of voltage comparator and adjustable voltage regulator that will supply the voltage that only needed by the battery and will then be disconnected automatically form the battery when it’s fully charged.In this project, analysis on the consumption of power and battery condition will be reported. Cutting off power supply enhancement was achieved by using the combination of two IC’s compared to a normal battery charger with only using simple power supply circuit.